Nitrogen cycling in the South Atlantic and South Indian Oceans investigated using nitrate isotopes: implications for nutrient supply, ocean fertility, carbon export, and climate - Marshall, Tanya (Department of Oceanography, 2024)
Bioavailable nitrogen (N) limits phytoplankton growth across much of the (sub)tropical ocean, thereby modulating ocean fertility and climate. Dinitrogen (N2) fixation is the dominant source of new N to the ocean and is thought to occur mainly in well-lit, warm, oligotrophic waters. The under-sampled South Atlantic and South Indian Ocean basins are predicted by models to host widespread N2 fixation; for the South Atlantic, this predication contradicts the limited available observations and for the South Indian, is yet to be confirmed by measurements. In this thesis, four new nitrate isotope datasets from the South Atlantic and South Indian Oceans are presented alongside coincident nutrient and hydrographic data, and other published nitrate isotope datasets. Combined, these data provide a means of quantifying the rate and distribution of N2 fixation, along with characterizing additional co-occurring N cycle processes, mechanisms of subsurface nutrient supply, and water mass circulation. Measurements of nitrate N isotope ratios (15N) and nutrient stoichiometry (i.e., nitrate to phosphate ratios; N:P) from a zonal transect of the tropical South Atlantic (at ~12S) and a meridional transect along the Angola margin (at ~12E) reveal an N2 fixation hotspot in the eastern tropical Angola Gyre. Here, thermocline nitrate 15N is low and N:P is high relative to the underlying source water and the western tropical basin thermocline. The N2 fixation rate estimated from the Angola Gyre nitrate 15N data of 1.4-5.4 Tg N.a-1 accounts for 28-108% of the rate predicted for the South Atlantic basin. These findings contradict recent model diagnoses of N2 fixation, which predict high rates in the western tropical basin and none to the east. The overlapping biogeography of a basin-wide P excess relative to N and bioavailable iron supplied locally from the Angola margin likely control N2 fixation in the Angola Gyre. Analogous conditions elsewhere in the ocean, such as in other eastern boundary shadow zones and retentive near-coast subtropical systems, should also favour N2 fixation. The western boundary current of the South Indian Ocean, the Agulhas Current, is the strongest boundary current on Earth, yet nutrient cycling in this subtropical system remains largely uncharacterized. Measurements of the dual isotope ratios (N and oxygen) of nitrate from within and upstream of the greater Agulhas region provide insights into regional circulation and N cycle dynamics. The nitrate isotopes reveal both local and remote signals of Indian Ocean N cycling such as denitrification in the Arabian Sea and partial nitrate assimilation in Southern Ocean surface waters, as well as evidence of local N2 fixation and coupled partial nitrate assimilation and nitrification. Using a one-box model to simulate the newly-fixed nitrate flux, the local N2 fixation rate for the greater Agulhas region is estimated to Thesis abstract be 7-25 Tg N.a-1; this value is the first observation-based N2 fixation rate estimate for the South Indian Ocean. Local N cycling imprints an isotopic signal on Indian Ocean nitrate that can be tracked beyond the Indian Ocean because it persists in Agulhas eddies that “leak” into the South Atlantic at the Agulhas Retroflection. If this signal is retained in plankton that sink to the seafloor, it could be used to reconstruct past Agulhas leakage, yielding quantitative insights into the strength of the Atlantic Meridional Overturning Circulation in the past. The Agulhas Current system, like other western boundary current systems, is characterised by high energy and turbulence. A novel application of the dual isotopes of nitrate reveals the occurrence of three (sub)mesoscale mechanisms of upward nitrate supply; entrainment at the edges of a mesoscale anticyclonic eddy, inshore upwelling likely driven by a frontal eddy, and overturning at the offshore edge of the current core likely driven by coupled mesoscalesubmesoscale instabilities. The intensity and (sub)surface expression of these nutrient supply events are not always apparent in the hydrographic data, highlighting the utility of the nitrate isotopes for exploring physical ocean processes. The conditions driving the nitrate supply mechanisms in the Agulhas region are common to western boundary currents, implying that the (sub)mesoscale vertical nitrate supply is quantitatively significant at the global scale. Additionally, these events of upward nitrate supply likely increase regional fertility in all western boundary current systems, with implications for the sustenance of higher trophic levels. Finally, increasing turbulence observed along mid-latitude western boundaries may enhance the upward nutrient supply to subtropical surface waters, and possibly compensate for the diminished productivity predicted as a result of increasing subtropical gyre stratification. Collectively, the work detailed in this thesis reveals the strong regionality of N cycling in the historically under-studied South Atlantic and South Indian Oceans, as well as the importance of interpreting biogeochemical data in the context of ocean dynamics across various scales. Improved predictions of N fluxes at the basin- and global scale, which are critical for estimating the ocean's CO2 sink and fertility, will require careful consideration of these southern basins so as not to mischaracterise their functioning, as has occurred in the past.